BACK TO BASICS: Nurturing Religious Moderation through the Co-Parenting Models of Islamic Education in Multicultural Indonesia - Jamilah, Jamilah; Walkaromah, Naylul Izzah (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2025)
This article seeks to discuss the role of co-parenting in shaping Islamic education within families and how this practice contributes to fostering social and religious harmony in a pluralistic society. This article employs a qualitative approach, collecting data through interviews with selected interlocutors to explore the parenting models used by each parent. This article argues that the co-parenting model emphasizes the cooperation of all family members, with effective communication serving as a crucial tool in building a holistic Islamic education that promotes harmony within the family. The article also highlights the importance of incorporating universal Islamic values into family education to shape children’s character and morals, aligning with sharia principles and promoting respect for diversity, thereby contributing to the harmonization of the religious and social spheres. Furthermore, the interviewees expressed a preference for both parents to be actively involved in the Islamic education process within the family environment. This desired involvement not only strengthens family ties but also creates a well-rounded learning experience for children. This study demonstrates that the stability of co-parenting provides a robust theoretical and empirical foundation to support the development of a model that can be applied in various Muslim family contexts, with the ultimate goal of fostering harmony within a broader religious dynamic.